Pengaruh Program Pembelajaran 12 Minggu terhadap Penguasaan Teknik Dasar Sepak Bola: Studi pada Siswa Sekolah Dasar - Irwan Shapryo; Herli Pardilla (Joska: Jurnal Isori Kampar, 2024)
Objectives: The research investigated the efficacy of football basic engineering programs on primary students and the influencing factors on skill mastery. Methods: The sample comprised 120 students (65 males, 55 females) from grades 4 and 5 engaged in a 12-week instructional program. The study assessed five fundamental techniques: ball control, passing, dribbling, shooting, and heading. A pre-test and post-test methodology was employed to evaluate skill enhancement through standardized assessments. Results: Findings indicated significant skill improvement (p<0.001) across all techniques, with ball control exhibiting the greatest enhancement (45%) and heading the least (25%). Factor analysis revealed a robust correlation between skill advancement and age (r=0.72) as well as exercise frequency (r=0.68), while gender did not demonstrate a significant impact (p=0.245). Notably, 85% of participants exhibited considerable progress in ball control, whereas heading techniques recorded a lower success rate (60%). Conclusion: The conclusion drawn posits that football basic engineering programs are effective in enhancing elementary students' skills, with age and training intensity identified as principal success factors.